Genesis and metallogenetic setting of the polymetallic barite-sulphide deposit, Bobija, Western Serbia - Maurer, Marcel; Prelević, Dejan; Mertz-Kraus, Regina; Pačevski, Aleksandar; Kostić, Bojan; Malbašić, Jovana (International journal of earth sciences : Geologische Rundschau, 2019)
The polymetallic Bobija ore deposit in Western Serbia is located at the southwestern edge of the Jadar Block, a distal part of the passive continental margin of Adria. The sulphide mineralization consists of fine-grained pyrite, sphalerite, galena and tetrahedrite, and is associated with abundant barite. The deposit is stratabound and hosted by a Triassic sedimentary sequence. A feeder zone is present in the immediate footwall of the ore mineralization. The volcano-sedimentary succession in the uppermost strata comprises coherent lavas and volcaniclastic sediments. They were investigated for the bulk rock composition and the zircons were subjected to U–Pb dating. Analysed zircons deliver an upper age limit of 243.1 ± 1.3 Ma. Sphalerite from the sulphide mineralization was investigated for its trace element content and pyrite and barite for their sulphur isotope composition. Sphalerite geothermometry indicates ore-bearing fluid temperatures of 152–179 °C. A negative δ 34 S value of − 6.3‰ in pyrite indicates a sulphur source from a partially reduced reservoir. The new data confirm a previously inferred Triassic age for the Bobija deposit and underline the importance of the prevalent rift regime for ore formation. We propose that the sediment-hosted Bobija deposit should be classified as a clastic-dominated, rift-related Pb–Zn deposit. Given the tectonic setting and temperature constraints, the hydrothermal processes are comparable to deposits classically referred to as sedimentary exhalative (SEDEX). This is in a good agreement with similar deposits occurring in Central Bosnia. These similarities reveal links between ore deposit formation and geodynamic evolution in the Balkan Peninsula, underlining the common geological evolution of the more external zones of the Dinarides and the Jadar Block.